2020
DOI: 10.5187/jast.2020.62.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loose farrowing facilities on reproductive performance in primiparous sows

Abstract: The present study investigated the effects of loose farrowing type during gestation and after farrowing on reproductive performance and of lactating sows. A total of 22 primiparous sows (Landrace; average initial body weights [BW], 228.54 ± 12.79 kg) were allotted to one of two treatments on the basis of body weight. Sows were divided into two experimental groups, conventional farrowing crates (CON), and loosed-farrowing pens (LFP). The experiment duration was around 38 days ranging from 10 days before parturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…While some studies have recorded an increased farrowing duration in sows confined from more than 2 days prior to expected farrowing in comparison with sows that were never confined or confined only after completion of farrowing ( 23 , 24 ), other studies have shown no difference ( 27 , 31 , 47 ), although the former two studies involved hyperprolific sows with much longer farrowings in both confined and unconfined conditions. In general, the consequences for the number of stillborn piglets have mirrored the effects on farrowing duration in the different studies, with three studies showing increased stillbirths in sows crated for more than 2 days before expected farrowing ( 23 , 24 , 47 ), although in the latter case, this was not associated with a longer farrowing duration or increased signs of birth stress (meconium staining, vigor) in newborn piglets. In contrast, six papers reported no difference in stillbirth rate ( 27 29 , 31 , 42 , 46 ), with all except the last of these involving hyperprolific sows.…”
Section: Management Choices In Temporary Crating Systemsmentioning
confidence: 97%
See 4 more Smart Citations
“…While some studies have recorded an increased farrowing duration in sows confined from more than 2 days prior to expected farrowing in comparison with sows that were never confined or confined only after completion of farrowing ( 23 , 24 ), other studies have shown no difference ( 27 , 31 , 47 ), although the former two studies involved hyperprolific sows with much longer farrowings in both confined and unconfined conditions. In general, the consequences for the number of stillborn piglets have mirrored the effects on farrowing duration in the different studies, with three studies showing increased stillbirths in sows crated for more than 2 days before expected farrowing ( 23 , 24 , 47 ), although in the latter case, this was not associated with a longer farrowing duration or increased signs of birth stress (meconium staining, vigor) in newborn piglets. In contrast, six papers reported no difference in stillbirth rate ( 27 29 , 31 , 42 , 46 ), with all except the last of these involving hyperprolific sows.…”
Section: Management Choices In Temporary Crating Systemsmentioning
confidence: 97%
“…From the perspective of the piglets, the most significant health parameter is absence of death or injury from crushing by the sow. Overall, most studies (12 out of 21) reported no statistically significant differences in piglet mortality rates between sows housed in temporary crates (opening D3–D14) and permanent farrowing crates ( 19 , 23 , 24 , 26 , 27 , 40 42 , 46 , 49 , 51 , 52 ) or zero confinement ( 33 ) ( Table 4 ). Four studies observed a decrease in piglet mortality in TC.…”
Section: The Interpretation Of Pig Welfare In Different Farrowing Sys...mentioning
confidence: 99%
See 3 more Smart Citations